Data from: Maternal winter body mass and not spring phenology determine annual calf production in an Arctic herbivore - Veiberg, Vebjorn; Loe, Leif Egil; Albon, Steve; Irvine, Robert; Tveraa, Torkild; Ropstad, Erik; Stien, Audun; Albon, Steve D.; Irvine, R. Justin (Zenodo, 2016)
Warming of the Arctic has resulted in earlier snowmelt and green-up of plants in spring, potentially disrupting the synchrony between plant phenology and breeding phenology in herbivores. A negative relationship between offspring survival in West-Greenland caribou and the timing of vegetation emergence was the first finding of such a mismatch in Arctic mammals. However, other studies indicate that the energy for foetal growth and early lactation is predominantly drawn from stored energy reserves typical of 'capital' breeders, suggesting that conditions well before spring influence calf production more than the timing of spring onset. Here we use 20 years of observations of marked Svalbard reindeer to evaluate determinants of annual recruitment, as measured by the presence of a calf at foot in mid-summer. Spring temperatures and the Enhanced Vegetation Index were used as proxies for spring onset, while data on body mass and pregnancy rates in late winter allowed us to determine maternal condition and the reproductive status before spring. Pregnancy rate, offspring survival and annual recruitment were all strongly correlated with average late winter adult female body mass (r = 0.87; r = 0.83; r = 0.92, respectively). Contrary to the findings in West Greenland, neither early calf survival nor annual recruitment were correlated with the two measures of annual variation in spring phenology (r= – 0.07, p = 0.8 and r = – 0.15, p = 0.6, respectively). We also revisit the Greenland data and reveal that the pattern of covariance between early and late measures of fecundity, as well as between early measures of fecundity and offspring survival, correspond with the results from Svalbard. Our results emphasize that conditions affecting maternal body mass during winter explain close to all the variation in recruitment, questioning the importance of the role of a mismatch between plant phenology and calving date. Annual body mass, reproduction and spring dates Annual estimates of the variables used in the analyses of the ...